Molecular basis for defining the pineal gland and pinealocytes as targets for tumor necrosis factor - Carvalho-Sousa, Claudia Emanuele (2010)
The pineal gland, the gland that translates darkness into an endocrine signal by releasing melatonin at night, is now considered a key player in the mounting of an innate immune response. Tumor necrosis factor (TNF), the first pro-inflammatory cytokine to be released by an inflammatory response, suppresses the translation of the key enzyme of melatonin synthesis (arylalkylamine-N-acetyltransferase, Aanat). Here, we show that TNF receptors of the subtype 1 (TNF-R1) are expressed by astrocytes, microglia, and pinealocytes. We also show that the TNF signaling reduces the level of inhibitory nuclear factor kappa B protein subtype A (NFKBIA), leading to the nuclear translocation of two NFKB dimers, p50/p50, and p50/RelA. The lack of a transactivating domain in the p50/p50 dimer suggests that this dimer is responsible for the repression of Aanat transcription. Meanwhile, p50/RelA promotes the expression of inducible nitric oxide synthase (iNOS) and the production of nitric oxide, which inhibits adrenergically induced melatonin production. Together, these data provide a mechanistic basis for considering pinealocytes a target ofTNF and reinforce the idea that the suppression of pineal melatonin is one of the mechanisms involved in mounting an innate immune response. © 2011 Carvalho-Sousa, da Silveira Cruz-Machado, Tamura, Fernandes, Pinato, Muxel, Cecon and Markus.